Modelling and Simulation of Packed Bed Catalytic Converter for Oxidation of Soot in Diesel Powered Vehicles Flue Gas - Nasikin, Mohammad; Wulan, Praswasti P.D.K.; Andrianty, Vita (Makara Journal of Technology, 2004)
Modelling and Simulation of Packed Bed Catalytic Converter for Oxidation of Soot in Diesel Powered Vehicles Flue Gas. Diesel vehicle is used in Indonesia in very big number. This vehicle exhausts pollutants especially diesel soot that can be reduces by using a catalytic converter to convert the soot to CO2. To obtain the optimal dimension of catalytic converter it is needed a model that can represent the profile of soot weight, temperature and pressure along the catalytic converter. In this study, a model is developed for packed bed catalytic converter in an adiabatic condition based on a kinetic study that has been reported previously. Calculation of developed equations in this model uses Polymath 5.X solver with Range Kutta Method. The simulation result shows that temperature profile along catalytic converter increases with the decrease of soot weight, while pressure profile decreases. The increase of soot weight in entering gas increases the needed converter length. On the other hand, the increase of catalyst diameter does not affect to soot weight along converter and temperature profile, but results a less pressure drop. For 2.500 c diesel engine, packed bed catalytic converter with ellipse’s cross sectional of 14,5X7,5 cm diagonal and 0,8 cm catalyst particle diameter, needs 4,1 cm length.